2017
DOI: 10.1055/s-0037-1603629
|View full text |Cite
|
Sign up to set email alerts
|

Cemented versus Cementless Total Hip Arthroplasty in Paget's Disease of Bone: A Systematic Review

Abstract: The purpose of this study is to systematically review the clinical evidence for the use of cemented and cementless total hip arthroplasty (THA) in Paget's disease of bone (PDB), and to ascertain whether any difference exists in clinical outcomes between the two implant types. MEDLINE, EMBASE, and the Cochrane Library databases were searched in accordance with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. The quality of the studies was assessed using the methodologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…However, bone cement can be challenging in these patients because of bone sclerosis contrasting cement penetration in the trabeculae, and also because of bone remodelling that could weaken the bone-cement interface [1]; for these reasons, the use of uncemented implants has been advocated [1,6]. In general, both cemented and uncemented implant revision and survival rates are similar [6,15]. In a recent review by Hanna et al [6], no difference in revision rates between cemented and uncemented implants was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, bone cement can be challenging in these patients because of bone sclerosis contrasting cement penetration in the trabeculae, and also because of bone remodelling that could weaken the bone-cement interface [1]; for these reasons, the use of uncemented implants has been advocated [1,6]. In general, both cemented and uncemented implant revision and survival rates are similar [6,15]. In a recent review by Hanna et al [6], no difference in revision rates between cemented and uncemented implants was found.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges related to surgery are due to the presence of bone sclerosis and deformities, the increased risk of periprosthetic fractures and the developing HO [6]. Implant fixation to the bone has been a matter for debate; bone cement has been widely used in the past, although some studies found a higher incidence of radiolucency at the bone-cement interface, and some authors support the use of uncemented implants [1,12,14,15]. At present, only one registry study is available on the topic, reporting about 114 patients operated on for THAs [16], but like in many registry studies, clinical outcomes are missing.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is limited literature on comparative studies of cemented versus cementless THA, Hurley at al. 23 performed a systematic review comparing the 2 fixation methods in patients with PBD, which included 13 case series with 444 primary THAs (111 cementless and 333 cemented). The study found that THA with cementless components had a significantly lower risk of aseptic loosening (1.8% [2 of 111] versus 24.6% [82 of 333]; p = 0.0002) and lower rates of revision (9.1% [1 of 11] versus 7.5% [25 of 333]; p = 0.0365) 23 .…”
Section: Cement Versus Cementlessmentioning
confidence: 99%
“…23 performed a systematic review comparing the 2 fixation methods in patients with PBD, which included 13 case series with 444 primary THAs (111 cementless and 333 cemented). The study found that THA with cementless components had a significantly lower risk of aseptic loosening (1.8% [2 of 111] versus 24.6% [82 of 333]; p = 0.0002) and lower rates of revision (9.1% [1 of 11] versus 7.5% [25 of 333]; p = 0.0365) 23 . It has been hypothesized that this is due to the vascularity of pagetoid bone, making it difficult to obtain the dry bone bed required for optimal cement penetration 63 .…”
Section: Cement Versus Cementlessmentioning
confidence: 99%
See 1 more Smart Citation